2002
DOI: 10.1046/j.1432-1033.2003.03362.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetics of the formyl‐methanofuran dehydrogenase and heterodisulfide reductase reactions in Methanothermobacter thermautotrophicus

Abstract: The synthesis of formyl-methanofuran and the reduction of the heterodisulfide (CoM-S-S-CoB) of coenzyme M (HS-CoM) and coenzyme B (HS-CoB) are two crucial, H 2 -dependent reactions in the energy metabolism of methanogenic archaea. The bioenergetics of the reactions in vivo were studied in chemostat cultures and in cell suspensions of Methanothermobacter thermautotrophicus metabolizing at defined dissolved hydrogen partial pressures ( p H 2 ). Formylmethanofuran synthesis is an endergonic reaction (DG°¢ ¼ +16 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
28
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 41 publications
7
28
0
1
Order By: Relevance
“…Under conditions of excess H 2 methanogens are capable of conserving some of the excess energy (de Poorter et al, 2003), but a larger portion is likely lost in the catabolic pathway and in concentration gradients (Sorensen et al, 2001). At the experimental conditions of this study, the Gibbs Free Energy yield (⌬GЈ) for catabolism is calculated to be Ϫ97 kJ mol Ϫ1 This "differential reversibility" hypothesis requires that the first five steps of the methanogenic pathway be fundamentally reversible under low H 2 conditions.…”
Section: Differential Reversibilitymentioning
confidence: 99%
“…Under conditions of excess H 2 methanogens are capable of conserving some of the excess energy (de Poorter et al, 2003), but a larger portion is likely lost in the catabolic pathway and in concentration gradients (Sorensen et al, 2001). At the experimental conditions of this study, the Gibbs Free Energy yield (⌬GЈ) for catabolism is calculated to be Ϫ97 kJ mol Ϫ1 This "differential reversibility" hypothesis requires that the first five steps of the methanogenic pathway be fundamentally reversible under low H 2 conditions.…”
Section: Differential Reversibilitymentioning
confidence: 99%
“…At regular time intervals, samples were collected anoxically for the determination of OD 600 , F 420 measurement, pH i determination and for cellsuspension incubations. The dissolved p H2 and medium pH were monitored online with an amperometric (Ag/Ag 2 O) H 2 probe (de Poorter et al, 2003;Schill et al, 1996) and a pH electrode (Ingold, Elscolab Nederlands BV), respectively. Alternatively, Methanothermobacter thermautotrophicus was cultured in 115 ml serum bottles containing 50 ml mineral medium supplemented with 0?6 g Na 2 S.2H 2 O l…”
mentioning
confidence: 99%
“…In fact, two distinct slopes could be observed depending on the p H2 value. Linear regression analysis then yielded Y CH4 max values of 3.1 Ϯ 0.3 and 3.1 Ϯ 0.1 g DW mol of CH 4 Ϫ1 for growth at a p H2 of ca. 1 and 5 kPa, respectively.…”
Section: Vol 73 2007 Methanogenesis and Growth Of M Thermautotrophmentioning
confidence: 99%
“…The baseline signal (0% H 2 ) was checked at the end of the fed-batch growth cycle and at regular occasions during the course of the continuous culturing by stopping the gas supply. Previous studies showed that under the conditions applied the intracellular hydrogen concentration equals the hydrogen concentration in the medium (3,4).…”
mentioning
confidence: 96%